AN ANALYSIS OF MICRO BUSINESS COMMUNITY INITIATIVES IN REVITALIZING MSMES POST-COVID-19 IN PURWAKARTA REGENCY - Thoriq, Arief Mulyawan; Ardiansyah, Hamdan; Ahmadiyah, Didih (Finansha: Journal of Sharia Financial Management, 2025)
This study examines the role of the Micro Business Community (MBC) as a community-based recovery mechanism for micro, small, and medium enterprises (MSMEs) in Purwakarta Regency in the post-pandemic period. The study aims to analyze how community collaboration, digital transformation, and social capital embedded within MBC contribute to MSME resilience and recovery after COVID-19. Using a qualitative interpretive approach, data were collected through observations, in-depth interviews, and document analysis involving 50 MSME actors across diverse business sectors. The findings indicate that MBC functions as an enabling platform that strengthens inter-firm collaboration, facilitates collective learning, enhances access to digital tools and resources, and supports coordinated problem-solving among MSMEs. These mechanisms collectively improve entrepreneurial resilience and adaptive capacity in a post-crisis environment. This study contributes conceptually by demonstrating how the Micro Business Community operationalizes community-based resilience through integrated collaboration, digitalization, and resource mobilization; contextually by providing empirical evidence from a post-pandemic MSME ecosystem in a developing regional setting; and methodologically by offering qualitative insights into community-driven recovery processes. The findings suggest that MBC represents a scalable model that can be adopted by local governments and integrated with Islamic microfinance institutions to support inclusive and sustainable MSME development in post-crisis contexts.